الازمة المالية و تاثيرها في فرض الحماية على المغرب الاقصى من 1959م الى 1912 م - فاطمة الزهراء عرابة; د/ محمد علاق (جامعة عمار ثليجي الاغواط, 2024)
الملخص: لقد تمحور موضوع دراستنا حول تأثير الازمة المالية في فرض الحماية على المغرب الاقصى (1859-1912م) وشهدت هذه الحقبة من الزمن ضغطا وتنافسا دولي شديد بين الدول الأوروبية حول النفوذ في المغرب الاقصى من أجل الحصول على امتيازات اقتصادية كلفت المغرب في سقوط في ازمة مالية بدأت معالمها من خلال فرض اسبانيا غرامات مالية على المغرب تعويضا لخسائر حرب تطوان 1860م، وقد سعى السلطان حسن الاول الى التقليص من حدة التنافس الاوروبي حول المغرب بقيامه بالعديد من الاصلاحات في مجالات مختلفة للحد من التطور الاوروبي وبعد وفاته سنة 1894م تولى الحكم ابنه المولاي عبد العزيز وعرف عهده بانتشار الفتن والاضطرابات وضعف المخزن ما جعله يصدر الترتيب العزيزي الذي زاد في غرق المغرب ونشوب التمردات وأخطرها ثورة بوحمارة 1902م التي أرهقت المخزن ما جعله يقع في فخ القروض (الاستدانة) التي كلفته فقدان الجزيرة لسيادة المغرب وبداية الاجتياح الاوروبي واستغلت فرنسا هذا الموقف من اجل السيطرة على المغرب من خلال القيام بالاتفاقيات الودية مع الدول الاوروبية من (1902-1904م) لإزاحة الطريق لفرنسا في المغرب وبعد التخلص من المعارضة الالمانية في المغرب سنة 1911م وذلك بمنح ألمانيا مساحات من أراضي الكونغو وهكذا تمكنت فرنسا واسبانيا بالانفراد في المغرب وفرض الحماية المزدوجة سنة 1912م. Abstract : The subject of our study revolved around the impact of the financial crisis on imposing protectionism on the Al-Aqsa Maghreb (1859-1912 AD). This period of time witnessed intense international pressure and competition between European countries over influence in the Al-Aqsa Maghreb in order to obtain economic privileges that cost Morocco a financial crisis that began. Its features include Spain imposing financial fines on Morocco to compensate for the losses of the Tetouan War of 1860 AD. Sultan Hassan I sought to reduce the intensity of European rivalry over Morocco by implementing many reforms in various fields to limit European development. After his death in 1894 AD, his son, Moulay Abdel Aziz, assumed power. His reign with the spread of strife and unrest and the weakness of the storehouse made him issue the Azizi Order, which increased the sinking of Morocco and the outbreak of rebellions, the most dangerous of which was the Bouhamara Revolution of 1902, which exhausted the storehouse, causing it to fall into the trap of loans (leveraging) that cost it the island’s loss of Moroccan sovereignty and the beginning of the European invasion. France exploited this situation in order to gain control. On Morocco, through friendly agreements with European countries from 1902-1904 AD, to clear the way for France in Morocco, and after getting rid of the German opposition in Morocco in 1911 AD, by granting Germany areas of Congo territory. Thus, France and Spain were able to seize control of Morocco and impose dual protection in 1912 AD.